Analisis Kekuatan Pasar Perusahaan Kayu Hexa Karya Utama di Wilayah Pasuruan - Ignatius Edward Revalyno; Muhammad Yasin (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This research aims to analyze the market power of the company PT. Hexa Karya Utama uses the Lerner Index as a measuring tool. The Lerner Index is an indicator that describes a company's ability to set prices above marginal costs, which reflects monopoly power and market power. In the context of the timber industry, where competition is increasingly fierce, understanding market forces is crucial for effective business strategies. The analysis results show that PT. Hexa Karya Utama has a significant Lerner Index value, which indicates quite good market strength.